2016
DOI: 10.5194/tc-10-133-2016
|View full text |Cite
|
Sign up to set email alerts
|

Climatic controls and climate proxy potential of Lewis Glacier, Mt. Kenya

Abstract: Abstract. The Lewis Glacier on Mt. Kenya is one of the best studied tropical glaciers and has experienced considerable retreat since a maximum extent in the late 19th century (L19). From distributed mass and energy balance modelling, this study evaluates the current sensitivity of the surface mass and energy balance to climatic drivers, explores climate conditions under which the L19 maximum extent might have been sustained, and discusses the potential for using the glacier retreat to quantify climate change. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 76 publications
0
30
1
Order By: Relevance
“…Rather than integrating the flux-gradient relations with a chosen parametrization for K, Oerlemans and Grisogono (2002) derived a bulk approach for surface heat fluxes through a simplified scaling of the governing equations for heat and momentum balance in a 1-D katabatic flow model (Prandtl, 1942). Their basic assumption was that the katabatic flow is characterized by a well-defined wind maximum, setting the exchange coefficient for heat proportional to the maximum wind speed and to the height of the wind maximum.…”
Section: Kat Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather than integrating the flux-gradient relations with a chosen parametrization for K, Oerlemans and Grisogono (2002) derived a bulk approach for surface heat fluxes through a simplified scaling of the governing equations for heat and momentum balance in a 1-D katabatic flow model (Prandtl, 1942). Their basic assumption was that the katabatic flow is characterized by a well-defined wind maximum, setting the exchange coefficient for heat proportional to the maximum wind speed and to the height of the wind maximum.…”
Section: Kat Methodsmentioning
confidence: 99%
“…The Prandtl model for katabatic flow that treats eddy viscosity as a constant value (Prandtl, 1942) is unable to correctly describe the sharp near-surface gradients in wind speed and air temperature that are often observed (Munro, 1989;Oerlemans, 1998). Grisogono and Oerlemans (2001) showed that the Prandtl model can be improved if a varying assigned eddy viscosity profile is used instead of a constant value.…”
Section: Stable Boundary Layers Accompanied By Katabatic Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…A fundamental obstacle in studying small-scale boundary layer characteristics is that, even on well-studied mountain glaciers, the deficiency of monitoring activities restricts the process understanding, required for detailed research, to a few sites and limited time periods (e.g., Wagnon et al, 1999;Mölg and Hardy, 2004;Obleitner and Lehning, 2004;Reijmer and Hock, 2008;Nicholson et al, 2013). The phenomenological knowledge that is valid for the specific location and weather situation does not have greater significance beyond the case (e.g., Machguth et al, 2006;Gardner et al, 2013;Zemp et al, 2013).…”
Section: T Sauter and S P Galos: Effects Of Local Advection On Thementioning
confidence: 99%
“…Countless studies aim to identify the climatic drivers behind observed glacier changes by using distributed mass and energy balance models (e.g., Arnold et al, 1996;Hock and Holmgren, 2005;Klok and Oerlemans, 2002;Mölg et al, 2009). While these kinds of models summarize our understanding of the governing physical processes at a point scale, they have proven insufficient to reflect the variability of the energy and mass fluxes on mountain glaciers (e.g., Gurgiser et al, 2013;MacDougall and Flowers, 2011;Prinz et al, 2016). The reduced spatial and temporal variability predominantly results from shortcomings in the representation of local processes in the forcing data.…”
Section: Introductionmentioning
confidence: 99%